ANALISIS OF THE INFLUENCE OF THE MAIN PARAMETERS AND CONDITION OF WORK OF AIRCRAFT CESN ON THE EFFICENCY OF THEIR USE METHODS OF MATHEMATICAL MODELING - V. I. Troitsky (Научный вестник МГТУ ГА, 2018)
The article describes the results of the numerical experiments on the mathematical model of the correlation-extreme navigation system (CESN) of the aircraft (LA) using microwave radiation of the earth's cover. The aim of the numerical experiments was the analysis of the influence of the main parameters (characteristics of the radiometer and antenna, a means of reviewing the space, parameters of the current image and the reference image, methods for image processing (algorithms for image correlation), conditions of the equipment operation (the speed and altitude of aircraft, the evolution of media) on the efficiency of CESN. The experiments were carried out with the fields of the underlying surface of three types-with an artificially synthesized map (CLAIM) containing several objects of different thermal contrast; with a homogeneous random field (OSP), with fragments of a digital map object structure (TSKOS) of real surface area of the earth. As a result of numerical experiments the author studied the influence on exactness characteristics of CESN navigation parameters (bank angles, pitch, yaw), flight altitude and speed, the noise of the radiometer, the pattern width, the width of the review sector, mis-scaling and angular misalignment of the current and reference images. Comparison of different methods of surface scanning was made based on the simulation results. During the experiments, the variation of one of the parameters with respect to the base variants of the parameters was carried out and the values and variances of errors of the CESN were estimated. All three main methods of beam scanning (longitudinal with a multi-beam radiometer, conical and transverse) were considered. The operation of the maximum search was made up of two procedures: searching for the global maximum area of the correlation matrix by enumerating all matrix entries and refining the location of the true maximum point by quadratic interpolation of the function. The implementation of errors is considered for various trajectories of the aircraft's motion, as well as for various angular variances. The implementation processing showed that an increase in the angular dispersion leads to a simultaneous increase in both the error modulus and the variance of the error modulus. The analysis of the obtained dependences shows a fairly stable tendency to reduce errors of CESN with a decrease in navigation angles. This dependence is demonstrated graphically. In order to estimate only the influence of the fluctuation noise of the radiometer on the magnitude of the CESN errors, a series of experiments was performed in which all other random fluctuations in the channel were eliminated.